Symmetrical solutions of hybrid nanofluid stagnation-point flow in a porous medium - Waini, Iskandar; Ishak, Anuar; Pop, Ioan (Elsevier Ltd, 2022)
This current study considers the hybrid nanofluid flow on a non-axisymmetric stagnation point region of a flat plate in a porous medium. By adopting the similarity variables, the equations that govern the flow are adapted to the similarity equations and then be solved by utilizing the bvp4c solver. Some samples of the friction factor and heat transfer rate, as well as the velocities and the temperature profiles, are presented. It is interesting to note that the friction factor for both x and y directions exhibits the symmetries pattern. Furthermore, the outcomes show that the friction factor increase with the rising of the hybrid nanoparticles and the porous medium parameter. Meanwhile, hybrid nanoparticles led to enhance the heat transfer rate but the porous medium parameter shows the opposite effect. Moreover, the value of the shear-to-strain-rate ratio where the occurrence of zero friction on the wall is also determined.